Halofuginone Attenuates Osteoarthritis by Rescuing Bone Remodeling in Subchondral Bone Through Oral Gavage - Mu, Wenbo; Xu, Boyong; Ma, Hairong; Li, Jiao; Ji, Baochao; Zhang, Zhendong; Amat, Abdusami; Cao, Li (Frontiers in Pharmacology, 2018)
Osteoarthritis (OA) is a common debilitating joint disorder worldwide without effective medical therapy. Articular cartilage and subchondral bone act in concert as a functional unit with the onset of OA. Halofuginone is analog of the alkaloid febrifugine extracted from the plant Dichroa febrifuga, which has been demonstrated to exert inhibition of SMAD 2/3 phosphorylation downstream of the TGF-β signaling pathway and osteoclastogenesis. To investigate whether halofuginone (HF) alleviates OA after administration by oral gavage, we allocated 3-month-old male mice to the Sham group, vehicle-treated anterior cruciate ligament transection (ACLT) group, and HF-treated ACLT group. The immunostaining analysis indicated that HF reduced the number of matrix metalloproteinase 13 (MMP-13) and collagen X (Col X) positive cells in the articular cartilage. Moreover, HF lowered histologic OA score and prevented articular cartilage degeneration. The micro-computed tomography (μCT) scan showed that HF normalized the subchondral bone microarchitecture demonstrated by the restoration of bone volume fraction (BV/TV), subchondral bone plate thickness (SBP.Th), and trabecular pattern factor (Tb.Pf) to a level comparable to that of the Sham group. Immunostaining for CD31 and μCT based angiography showed that the number and volume of vessels in subchondral bone was restored by HF. HF administered by oral gavage recoupled bone remodeling and inhibited aberrant angiogenesis in the subchondral bone, further slowed the progression of OA. Therefore, HF administered by oral gavage could be a potential therapy for OA.